Electrocardiogram Changes with Acute Alcohol Intoxication: A Systematic Review - Raheja, Hitesh (Open Cardiovasc Med J, 2018)
BACKGROUND: Acute alcohol intoxication has been associated with cardiac arrhythmias but the electrocardiogram (ECG) changes associated with acute alcohol intoxication are not well defined in the literature. OBJECTIVE: Highlight the best evidence regarding the ECG changes associated with acute alcohol intoxication in otherwise healthy patients and the pathophysiology of the changes. METHODS: A literature search was carried out; 4 studies relating to ECG changes with acute alcohol intoxication were included in this review. RESULTS: Of the total 141 patients included in the review, 90 (63.8%) patients had P-wave prolongation, 80 (56%) patients had QTc prolongation, 19 (13.5%) patients developed T-wave abnormalities, 10 (7%) patients had QRS complex prolongation, 3 (2.12%) patients developed ST-segment depressions. CONCLUSION: The most common ECG changes associated with acute alcohol intoxication are (in decreasing order of frequency) P-wave and QTc prolongation, followed by T-wave abnormalities and QRS complex prolongation. Mostly, these changes are completely reversible.